Glycosylation of viral surface proteins probed by mass spectrometry - Hargett, Audra A (Curr Opin Virol, 2019)
Glycosylation is a common and biologically significant post-translational modification that is found on numerous virus surface proteins (VSPs). Many of these glycans affect virulence through modulating virus receptor binding, masking antigenic sites, or by stimulating the host immune response. Mass spectrometry (MS) has arisen as a pivotal technique for the characterization of VSP glycosylation. This review will cover how MS-based analyses, such as released glycan profiles, glycan site localization, site-occupancy, and site-specific heterogeneity, are being utilized to map VSP glycosylation. Furthermore, this review will provide information on how MS glycoprofiling data are being used in conjunction with molecular and structural experiments to provide a better understanding of the role of specific glycans in VSP function.